Evidence of a Christmas spirit network in the brain: functional MRI study. (16th December 2015) - Hougaard, Anders; Lindberg, Ulrich; Arngrim, Nanna; Larsson, Henrik B W; Olesen, Jes; Amin, Faisal Mohammad; Ashina, Messoud; Haddock, Bryan T
Abstract : Objective  To detect and localise the Christmas spirit in the human brain. Design  Single blinded, cross cultural group study with functional magnetic resonance imaging (fMRI). Setting  Functional imaging unit and department of clinical physiology, nuclear medicine and PET in Denmark. Participants  10 healthy people from the Copenhagen area who routinely celebrate Christmas and 10 healthy people living in the same area who have no Christmas traditions. Main outcome measures  Brain activation unique to the group with Christmas traditions during visual stimulation with images with a Christmas theme. Methods  Functional brain scans optimised for detection of the blood oxygen level dependent (BOLD) response were performed while participants viewed a series of images with Christmas themes interleaved with neutral images having similar characteristics but containing nothing that symbolises Christmas. After scanning, participants answered a questionnaire about their Christmas traditions and the associations they have with Christmas. Brain activation maps from scanning were analysed for Christmas related activation in the "Christmas" and "non-Christmas" groups individually. Subsequently, differences between the two groups were calculated to determine Christmas specific brain activation. Results  Significant clusters of increased BOLD activation in the sensory motor cortex, the premotor and primary motor cortex, and the parietal lobule (inferior and superior) were found in scans of people who celebrate Christmas with positive associations compared with scans in a group having no Christmas traditions and neutral associations. These cerebral areas have been associated with spirituality, somatic senses, and recognition of facial emotion among many other functions. Conclusions  There is a "Christmas spirit network" in the human brain comprising several cortical areas. This network had a significantly higher activation in a people who celebrate Christmas with positive associations as opposed to a people who have no Christmas traditions and neutral associations. Further research is necessary to understand this and other potential holiday circuits in the brain. Although merry and intriguing, these findings should be interpreted with caution.